The Palestinian State: International Legal Context - Атнашев, Вадим (Научни трудове, 2018)
The paper considers some key issues concerning international recognition of the Palestine as an independent state and prospects of its gaining real sovereignty. The conclusion is that the Israeli-Palestinian conflict is an undulating process, so the task of minimizing conflict requires the ability to take advantage of a decline in the level of confrontation, when both sides are ready for mutual concessions.